2021
DOI: 10.3390/v13091851
|View full text |Cite
|
Sign up to set email alerts
|

The Pathobiology of H7N3 Low and High Pathogenicity Avian Influenza Viruses from the United States Outbreak in 2020 Differs between Turkeys and Chickens

Abstract: An outbreak caused by H7N3 low pathogenicity avian influenza virus (LPAIV) occurred in commercial turkey farms in the states of North Carolina (NC) and South Carolina (SC), United States in March of 2020. Subsequently, H7N3 high pathogenicity avian influenza virus (HPAIV) was detected on a turkey farm in SC. The infectivity, transmissibility, and pathogenicity of the H7N3 HPAIV and two LPAIV isolates, including one with a deletion in the neuraminidase (NA) protein stalk, were studied in turkeys and chickens. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…The spread and replication of the LPAIV among turkeys eventually resulted in the emergence of a HPAIV by the acquisition of basic amino acids at the hemagglutinin (HA) cleavage site. The H7N3 LPAIV-1, LPAIV-2, and HPAIV used in this study, as well as all viruses sequenced from the outbreak, were shown to be highly related to each other, with over 99 percent sequence identity across all segments [ 30 , 35 ]. LPAIV-1 and HPAIV belong to the major group of viruses identified from the outbreak called Cluster A, while LPAIV-2 belongs to a smaller group of viruses called Cluster B, in which the neuraminidase (NA) segment had a 66-nucleotide deletion in the stalk region of the NA gene [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The spread and replication of the LPAIV among turkeys eventually resulted in the emergence of a HPAIV by the acquisition of basic amino acids at the hemagglutinin (HA) cleavage site. The H7N3 LPAIV-1, LPAIV-2, and HPAIV used in this study, as well as all viruses sequenced from the outbreak, were shown to be highly related to each other, with over 99 percent sequence identity across all segments [ 30 , 35 ]. LPAIV-1 and HPAIV belong to the major group of viruses identified from the outbreak called Cluster A, while LPAIV-2 belongs to a smaller group of viruses called Cluster B, in which the neuraminidase (NA) segment had a 66-nucleotide deletion in the stalk region of the NA gene [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, virus-inoculated turkeys transmitted the viruses to all contacts regardless of the virus doses tested, whereas transmission was only observed in chickens inoculated with either of the two LPAIVs at the highest virus doses tested. These results demonstrate that turkeys are more susceptible to the 2020 H7N3 viruses compared to chickens [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations